Being an impact champion : enacting corporate social consciousness - Rajeev, Priya Nair; Joy, Simy (India : Penguin Random House, 2023)
"Social consciousness is a mindset that understands and accepts the interconnectedness of the economic, social and natural environments. Socially conscious managers make socially conscious organizations. Being an Impact Champion lays out three pathways for managers to enact their social consciousness-corporate social responsibility, corporate social innovations, and social entrepreneurship-to create impact. These ideas will instill confidence in new managers to initiate conversations on social and environmental issues facing the corporate world and expand their capacity to initiate and influence change"--